Geopolitics of Artificial Intelligence: Technology Controls and The Fragmentation of Global Order - Rezky Ramadhan Antuli (PENA KREATIF PUBLISHER, 2026)
Artificial intelligence (AI) has emerged as a strategic arena where technological capability increasingly determines geopolitical influence, economic resilience, and institutional authority. While existing studies have extensively examined AI governance, technological competition, and digital sovereignty, they largely treat technology controls as security or regulatory instruments rather than as mechanisms that actively reshape the international order. This article addresses that gap by proposing a geopolitical order framework that explains how AI technology controls generate systemic fragmentation through the reconfiguration of technological dependencies, institutional authority, and strategic inclusion. Using a qualitative research design based on document analysis, the study examines policy documents, regulatory frameworks, official government publications, and scholarly literature concerning AI governance, export controls, supply-chain politics, investment restrictions, and global technology regulation. The analysis demonstrates that technology controls extend beyond defensive policy measures to function as instruments of geopolitical ordering that selectively regulate access to critical AI infrastructures, reinforce hierarchical technological relationships, and institutionalize differentiated patterns of global connectivity. The study argues that fragmentation should not be understood merely as technological decoupling or bloc competition, but as a layered political process characterized by selective inclusion, asymmetrical interdependence, and differentiated authority within the global AI ecosystem. By conceptualizing technology controls as mechanisms of order formation rather than solely instruments of strategic competition, this article advances a theoretical framework that bridges AI governance and geopolitical order studies while providing a more comprehensive explanation of how contemporary technological rivalry is restructuring the architecture of global order.